Efficacy of Proximal Femoral Nail Antirotation (PFNA) in the Fixation of Intertrochanteric Femoral Fractures: A Prospective Study on 40 Patients: Efektivitas Antirotasi Kuku Femur Proksimal (PFNA) pada Fiksasi Fraktur Femur Intertrokanterik: Sebuah Studi Prospektif pada 40 Pasien - AL-Shwilly, Ali A. H.; AL-Shwilly, Hatim A. J. (Indonesian Journal on Health Science and Medicine, 2025)
Background: Intertrochanteric femoral fractures are common in the elderly population and pose significant challenges in orthopedic surgery. The Proximal Femoral Nail Antirotation (PFNA) has emerged as a promising fixation method, offering biomechanical advantages in the management of these fractures. This study evaluates the effectiveness and outcomes of PFNA in patients with intertrochanteric femoral fractures. Aim: To assess the clinical outcomes, healing efficacy, and complication rates associated with the use of PFNA in the fixation of intertrochanteric femoral fractures. Patients and Methods: In this prospective study, 40 patients with intertrochanteric femoral fractures were treated using PFNA. The cohort was monitored for a follow-up period of 12 months post-surgery. Key outcome measures included fracture union time, functional recovery using the Modified Harris Hip Score, and the incidence of postoperative complications. Results: All 40 patients successfully underwent intertrochanteric femoral fracture fixation with PFNA. The average time to fracture union was observed to be within the expected range for this patient population. Functional recovery, as measured by the Modified Harris Hip Score, showed significant improvement over the 12-month follow-up period. The complication rate was minimal, with only a few cases experiencing minor, manageable complications. There was no incidence of implant failure or significant postoperative morbidity. Conclusion: The study demonstrates that PFNA is a reliable and effective method for fixing intertrochanteric femoral fractures, providing satisfactory stabilization, timely bone healing, and low complication rate. It supports its use as a treatment option, but further studies with larger sample sizes and longer follow-up periods are recommended. Highlights: Evaluate PFNA effectiveness in intertrochanteric femoral fracture fixation. Prospective study, 40 patients, 12-month follow-up, functional recovery assessed. PFNA ensures stable fixation, timely healing, and low complication rates. Keywords: PFNA, intertrochanteric femoral fractures, fixation, functional recovery, complication rate